Model of Conflict Resolution with Social Capital in the Development of Genilangit Tourism Village, Poncol District, Magetan Regency, East Java Province - Agung Wibowo; Eny Lestari; Sugihardjo Sugihardjo (Jurnal Penyuluhan, 2020)
Tourism Village of Genilangit can be regarded as one form Community based tourism but in the process of rural tourism development can not be separated from the dynamics of the conflict. This study aimed to analyze the existence of social capital plays an important role in resolving the conflict. This study chose the area on the southern slope of Mount Lawu in Genilangit Village in Poncol District, Magetan Regency. The main basis for the selection of this region is that the development of the Genilangit Tourism Village is the initiator of the local community with the cost and energy of the local community. his research embraces paradigm constructivist with qualitative methods. This research uses a case study, which is an empirical inquiry investigating the strength of social capital values in line with the development of a tourism village. Data analysis was performed by uniting the two approaches is the structural-functional theory and the theory of conflict. The results showed that the values of social capital that are still stored on the community becomes a powerful weapon in conflict resolution in the construction of a tourist village. Entities of social capital in this study from the aspect of participation in a network, resiprocity, trust, values, norms that exist in the local community. social capital is the basis in preparing models of conflict resolution in rural development Tourism Village of Genilangit.